2012
DOI: 10.1007/s00228-012-1449-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the UGT2B7 -161C>T polymorphism on the population pharmacokinetics of lamotrigine in Thai patients

Abstract: Both genetic and non-genetic factors were found to influence lamotrigine pharmacokinetics. These factors should be considered when determining lamotrigine dosing. The model presented here could be useful for lamotrigine dose adjustment in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
44
5
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 25 publications
5
44
5
2
Order By: Relevance
“…In Caucasians, there are two polymorphisms that lead to amino acid changes, UGT1A4 70C[A (rs#: 6755571) and the UGT1A4 142T[G (rs#: 2011425), with allelic frequencies of 4.9-8.8 and 8.3-11 %, respectively [17,19,20]. They are in linkage disequilibrium and have been associated with reduced in vitro glucuronidation activities against different substrates, including LTG [15,17,19,[21][22][23]. Our patient was homozygous for UGT1A4-70C, and this cannot account for higher LTG levels, since patients carrying this wild-type genotype would exhibit a higher clearance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Caucasians, there are two polymorphisms that lead to amino acid changes, UGT1A4 70C[A (rs#: 6755571) and the UGT1A4 142T[G (rs#: 2011425), with allelic frequencies of 4.9-8.8 and 8.3-11 %, respectively [17,19,20]. They are in linkage disequilibrium and have been associated with reduced in vitro glucuronidation activities against different substrates, including LTG [15,17,19,[21][22][23]. Our patient was homozygous for UGT1A4-70C, and this cannot account for higher LTG levels, since patients carrying this wild-type genotype would exhibit a higher clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it been suggested that, beside other factors (e.g., age, concurrent disease, body size, co-medications, pregnancy status, ethnicity), also UGT1A4, UGT2B7 and ABCB1 variants may also influence the pharmacokinetics of LTG and, consequently, explain its inter-individual variability [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations